Effectiveness of Corporate Governance and Audit Quality: The Role of Ownership Concentration as Moderation - Natasya Adela Widani; Yustrida Bernawati (ETIKONOMI, 2020)
The case of corporate financial statement fraud committed by company management is a phenomenon that often occurs and occurs repeatedly. This condition is exacerbated by the involvement of external auditors to support the fraud. This study aims to determine the effect of corporate governance and audit quality and find out the ownership concentration moderating corporate governance and audit quality. This study uses moderated regression analysis and research samples on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2018. The results of the study stated that corporate governance did not affect audit quality, and the presence of ownership concentration strengthened the effect of the effectiveness of corporate governance on audit quality. The implication of this research is to minimize earnings management practices. The effectiveness of corporate governance expects to run well and regulate the composition of ownership into something fundamental to implement.JEL Classification: G32, G34How to Cite:Widani, N. A., & Bernawati, Y. (2020). Competitive Strategy Analysis to Increase Consumer Purchasing Decisions on Minimarket Business. Etikonomi: Jurnal Ekonomi, 19(1), 131 – 140. https://doi.org/10.15408/etk.v19i1.14893.